Legitimizing Crisis Management during COVID-19 - Ruth Wodak (Argumentation et Analyse du Discours, 2022)
Mid-March 2020, European governments (and beyond) could not deny the Covid-19 dangerous pandemic anymore; they had to quickly cope with the crisis. Different modes of crisis communication have been adopted by government leaders to persuade people to abide by various measures to counteract the spreading of the virus, and thus to reduce fears and uncertainties. Some measures implied severe restrictions of human rights (such as freedom of movement, and so forth). Therefore, different legitimation strategies were applied to create society-wide consensus that such measures were indeed necessary. Some governments have also instrumentalized the pandemic for their authoritarian aims. This paper analyzes various strategies of legitimation, following the approach first developed by Van Leeuwen and Wodak (1999) and elaborated in Wodak (2018, 2021). In this way, legitimation is linked to specific argumentation schemes, always in context-dependent ways. The data for this paper stem from governmental speeches and press conferences in Austria, Hungary, Sweden, New Zealand, and France, in the period of March 2020 until December 2020.